Doença peri-implantar e níveis dos marcadores salivares IL-1ß, IL-10, RANK, OPG, MMP-2, TGF e TNF-: estudo observacional de 5 anos e revisão sistemática - Alex Martins Gomes (2018)
Peri-implant disease and levels of salivary biomarkers IL-1, IL-10, RANK, OPG, MMP-2, TGF and TNF-: a 5 years follow-up and systematic review Recent literature presents numerous studies on the association between peri-implant diseases (DPi) and levels of inflammatory biomarkers in peri-implant sulcus fluid, in gingival tissue and blood biopsies. Surprisingly, rare are studies on salivary markers related to the presence and progression of DPi, since saliva is abundant, its collection is an easy, low cost and, non-invasive method. In this sense, this thesis presents two distinct studies. The first (longitudinal) study that aimed to evaluate the peri-implant clinical condition and levels of the salivary markers IL 1, IL-10, RANK, OPG, MMP-2, TGF, and TNF- in individuals in the presence and absence of periodontal/ peri-implant maintenance (TMPP). The second study, a systematic review, focused in answer the following question: Could biomarker levels in the saliva help to distinguish between healthy implants and implants with peri-implant disease? The longitudinal study methodology involved 80 individuals diagnosed with mucositis (MP), who were divided into two groups: a group that underwent periodontal and peri-implant maintenance therapy, called GTP (n = 39), and a second group without regular maintenance, called GNTP (n = 41). Each participant underwent a complete periodontal and peri-implant clinical examination [recording of the clinical level of insertion (NCI), periodontal probing depth (PS) and peri-implant probing depth (PSI), periodontal bleeding (SS) and peri-implant bleeding (SSi), suppuration (SU); periodontal plaque (IP) and peri-implant plaque (IPi) indexes], radiographic examination for evaluation of peri-implant bone levels and collection of saliva samples at two times: initial examination (T1) and after 5 years (T2). The salivary samples were frozen and then evaluated by ELISA's method for the following markers: IL 1, IL-10, RANK, OPG, MMP- 2, TGF and TNF-. Results: A higher incidence of peri-implantitis (PI) was noted in the GNTP group (43.9%) than in the GTP group (18%) (p = 0.000). All the individuals (n = 12) who presented resolution of MP in T2 were from the GTP group. There was an increase in the number of individuals with periodontitis in GNTP when comparing T1 (22.0%) to T2 (41.5%) (p = 0.001). The result of the study revealed an increase in the salivary concentration of TNF- in GNTP compared to GTP. The other salivary markers evaluated did not show statistically significant alteration between the two groups. Conclusion: The absence of regular consultations for periodontal / peri-implant maintenance was associated with worse periodontal and peri-implant clinical condition, higher incidence of PI, and a significant increase in TNF- levels: suggesting this promising salivary marker for the prognosis and diagnosis of DPi.Additionally, the systematic review has shown that there is no solid evidence to conclude that salivary biomarkers could help distinguish between healthy implant implants with PI. Besides that, it is suggested that the results should be interpreted with caution due to the inclusion of many studies, in the systematic review, with a high risk of bias.